Biological control of Leptopharsa gibbicarina (Hemiptera: Tingidae) with the ant Crematogaster sp. (Hymenoptera: Formicidae) in oil palm - MONTAÑEZ, MARTHA LUCÍA; CALVACHE-GUERRERO, HUGO; CUQUE-Z., JESÚS EMILIO; MÉNDEZ, ADALBERTO (Revista Colombiana de Entomología, 1998)
This work was carried out on the farm "Las Delicias" in Ciénega, (Mag.), from January to September. 1995. The objective was to evaluate Crematogaster sp.ant predation on the Leptopharsa gibbicarina Froeschner bug, which induces "Pestaintiopsis" on palm leaves. The area with the highest bug population was selected, according to preestablished levels (high: 12 or more, Medium: 11-8, and Low 70 average bugs per leaf). Field evaluation of predation by Crematogaster sp. on bugs was made. Folioles with different instars of L. gibbicarina were taken and placed on ant paths on the palm stipe, to evaluate ant behavior toward bugs. Also. a sampling of bug population, an introduction of nests with ant colonies on the Palco stipe and monthly monitoring of the bug population to determine the level of ant control was made. The results show that Crematogaster sp. decreases the bug population to low levels by predation. The low index of bug population foud by the end of the period shows the importance of using Crentatogaster sp. colonies as part of integrated pest management and biological control of L. gibbicarina.